"Let's think together!" (a review of dialogue in the workplace). - Marais, John (My University, 2010)
This thesis explores a conceptual understanding of dialogue within a community of practice. It argues that meaningful conversations are at the core of critical, reflective, and analytical praxis, and that a critical understanding holds transformative possibilities for teaching and learning. Aspects of western and ethnic paradigms and their theoretical constructs, which may either enhance or hinder current practices, are identified, as are elements that arise from several case studies drawn from a large banking organisation operating out of South Africa. It is hoped that an evaluation of the research findings will provide a basis for an understanding of dialogue within a local context and that, further, it will provide a platform for extended dialogical exploration and research.
Keywords: Case study; Community of practice; Conceptual understanding; Critical, reflective, and analytical praxis; Critical understanding; Dialogue; Theoretical constructs; Western and ethnic paradigms